Ручное оружие дальнего боя Х – ХIII вв. на территории между Верхним Сиретом и Средним Днестром - Возний, Ігор (Tyragetia. Archeologie. Istorie. Antică. Serie Nouă. Chişinău., 2022)
The article considers the main categories of arrowheads of the 10th - late 13th centuries, found on archeological sites in the area between the Upper Siret and the Middle Dniester. The characteristics of the tips are given according to the way of their hafting (stem and socket tang), the cross-section of the head (flat and faceted) and the function. Among the stem points, we can single out flat, armor-piercing, Mongol-Tatar and bone ones, which are divided into separate types. The typology of socket points is analyzed. Their comparison was made and analogies were traced in other territories of the Old Rus state. The components of the bow and quiver found in the study area are considered. Designs of crossbows and ways of their application are characterized. The typology of crossbow bolts is carried out. Their feature, in contrast to the arrows of the bow, is the massiveness of the warhead. All crossbow bolts are armor-piercing, square, or rhombic in cross-section. Depending on the weight and size of the points, different types of crossbows were used. Accordingly, heavy crossbows such as a tour, pied de biche, and cric could be used in the study area. It is concluded that the long-range hand weapons found in the region under consideration were quite highly developed and their evolution took place in the general direction of the development of the military art of Eastern Europe.
Keywords: arrowhead; Mongol-Tatar srezen; tomar; armor-piercing point; two-horned srezen; aurel leaf shaped arrowhead; awl-shaped arrowhead; crossbow; a crossbow bolt